Chemical Composition and Biological Properties of Two Jatropha Species: Different Parts and Different Extraction Methods - Gokhan Zengin; Mohamad Fawzi Mahomoodally; Kouadio Ibrahime Sinan; Gunes Ak; Ouattara Katinan Etienne; Jugreet B. Sharmeen; Luigi Brunetti; Sheila Leone; Simonetta Cristina Di Simone; Lucia Recinella; Annalisa Chiavaroli; Luigi Menghini; et al. (MDPI AG, 2021)
Jatropha L. species, in particular, J. curcas and J. gossypiifolia, are well known medicinal plants used for treating various diseases. In the present study, leaf and stem bark extracts of J. curcas and J. gossypiifolia obtained by maceration or homogenizer assisted extraction, were investigated for their phytochemical contents and biological potential as antioxidants, enzyme inhibitors and neuromodulators. In this regard, the gene expression of tumor necrosis factor α (TNFα) and brain-derived neurotrophic factor (BDNF) was investigated in hypothalamic HypoE22 cells. Finally, a bioinformatics analysis was carried out with the aim to unravel the putative mechanisms consistent with both metabolomic fingerprints and pharmacological effects. The leaf extracts of J. curcas showed higher total phenolic content (TPC) and total flavonoid content (TFC) than the stem bark extracts (range: 5.79-48.95 mg GAE/g and 1.64-13.99 mg RE/g, respectively), while J. gossypiifolia possessed TPC and TFC in the range of 42.62-62.83 mg GAE/g and 6.97-17.63 mg RE/g, respectively. HPLC-MS/MS analysis revealed that the leaf extracts of both species obtained by homogenizer assisted extraction are richer in phytochemical compounds compared to the stem bark extracts obtained by the same extraction method. In vitro antioxidant potentials were also demonstrated in different assays (DPPH: 6.89-193.93 mg TE/g, ABTS: 20.20-255.39 mg TE/g, CUPRAC: 21.07-333.30 mg TE/g, FRAP: 14.02-168.93 mg TE/g, metal chelating activity: 3.21-17.51 mg EDTAE/g and phosphomolybdenum assay: 1.76-3.55 mmol TE/g). In particular, the leaf extract of J. curcas and the stem bark extract of J. gossypiifolia, both obtained by homogenizer assisted extraction, showed the most potent antioxidant capacity in terms of free radical scavenging and reducing activity, which could be related to their higher TPC and TFC. Furthermore, anti-neurodegenerative (acetylcholinesterase inhibition: 1.12-2.36 mg GALAE/g; butyrylcholinetserase inhibition: 0.50-3.68 mg GALAE/g), anti-hyperpigmentation (tyrosinase inhibition: 38.14-57.59 mg KAE/g) and antidiabetic (amylase inhibition: 0.28-0.62 mmol ACAE/g; glucosidase inhibition: 0.65-0.81 mmol ACAE/g) properties were displayed differentially by the different extracts. Additionally, the extracts were effective in reducing the gene expression of both TNFα and BDNF, which could be partially mediated by phenolic compounds such as naringenin, apigenin and quercetin. Indeed, the scientific data obtained from the present study complement the several other reports highlighting the pharmacological potentials of these two species, thus supporting their uses as therapeutically active plants.